Enzyme-Based Single Solid-State Nanochannel Biosensors - Hernández Parra, Luis Miguel (2025)
Sensing technologies play a critical role in healthcare, not only for diagnosis and treatment but especially for prevention and early intervention. Recent advances in biology, medicine, and materials science have expanded the landscape of measurable biological markers and enabled the development of nanotechnology-based biosensing platforms. Among the most prominent strategies in biosensing are those that take inspiration from nature, particularly through the integration of biological components such as enzymes. This review focuses on the intersection between enzymatic catalysis and single solid-state nanochannel (SSN) technologies as a promising approach for the development of advanced biosensing devices. We provide an overview of the historical background, current state of the art, and major achievements in enzyme-based biosensors and artificial nanochannel platforms, highlighting their synergistic potential. Particular attention is given to the challenges associated with enzyme integration into artificial environments, including stability and functionality retention, and the strategies employed to overcome them. Finally, we discuss the prospects and limitations of combining enzymes with SSNs, aiming to inspire future research in this emerging and multidisciplinary field.